الاجتهاد ودوره في فهم الواقع عند محمد إقبال الاجتهاد ودوره في فهم الواقع عند محمد إقبال (Al-Ijtihad wa Dauruhu fi Fahmi al- Waqi ‘Inda Muhammad Iqbal) - Lalu Supriadi Bin Mujib (Laboratorium Prodi Pendidikan Agama Islam UNJ, 2021)
This article presents Muhammad Iqbal's thoughts on the role of ijtihad in understanding the reality of modern life. This article aims to analyze and explain the life history of Muhammad Iqbal and his thoughts on the role of ijtihad in understanding the reality of modern life. This article uses a library research approach (library study) with a descriptive analytical method. The data derived from primary data sources and secondary data sources. The data were obtained by means of documentation utilizing the previous results of research written in books and journals. This article concludes that Muhammad Iqbal was a visionary Muslim figure and thinker who made a real contribution to the field of ijtihad. This visionary view succeeded in synergizing his knowledge and experience both conceptually and practically to solve the problems faced by Muslims. Ijtihad which plays a role in understanding the reality of modern life is collective ijtihad, that is, an ijtihad which is not limited by particular schools of thought and certain schools of jurisprudence, but rather an ijtihad that involves multi-skills and knowledge both in the fields of Islamic studies and science to achieve the benefit of the people ‘maslahah’. Collective ijtihad is currently appearing in the form of various fatwa institutions in the world, both in countries where the majority of the population is Muslim or in the minority.